Histopathological confirmation of disseminated larvae (iL3) of Strongyloides ratti in an immunosuppressed Wistar rat - Mahmuda A.; Al-Zihiry K.J.K.; Roslaini A.M.; Rukman A.H.; Abdulhaleem N.; Bande F.; Mohammed A.A.; Alayande M.O.; Abdullah W.O.; Zasmy U. (Malaysian Society for Parasitology, 2024)
Indexed by SCOPUS